Implementasi Promosi Pengasuhan dan Promosi Perlekatan pada Postpartum dengan Masalah Keperawatan Kesiapan Peningkatan Menjadi Orang Tua : Studi Kasus - Musviro Musviro; Lili Nur Azlina; Sri Wahyuningsih; Nurul Hayati; Rizeki Dwi Fibriansari (KHD Production, 2024)
Parents must prepare emotionally and psychologically to face pregnancy, childbirth, and parenting so that they can be more confident about their role as parents later. Parents' duties include providing exclusive breast milk, which has benefits for their baby's health, but there are still many mothers who experience failure in breastfeeding at the beginning of the birth of their first baby. This research aims to provide nursing care to postpartum mothers with nursing problems of readiness to become parents using a parenting promotion and attachment promotion approach (breastfeeding technique education) in the lotus room at RSUD Dr. Haryoto Lumajang. Data collection was used through interviews, observation, and documentation studies. Research shows that if care promotion and attachment promotion (education on breastfeeding techniques) are carried out in accordance with the SDKI, SLKI and SIKI guidelines, nursing problems can be resolved, and the role of parents can improve. Actions to promote nurturing and promotion of breastfeeding attachment/attachment techniques are very important to help mothers find it easier to breastfeed their children because more information can increase parents' knowledge and skills, thus creating awareness to change behaviour according to their knowledge.